The Design of Solar Power Tree in Tourist Village Area in Situgede Village, Karangpawitan Subdistrict, Garut Regency - Muhammad Gilang Prawira Darajat; Teguh Arfianto (Institut Teknologi Nasional, Bandung, 2022)
Energy is a basic need for every human being in the world, including in Situgede Village which is located in Karangpawitan Subdistrict, Garut Regency. According to the design concept of the Situgede village as a tourist village, there would be built a solar power plant forwhich construction aconcept of Solar Power Treewas designed. The methods employed in the design process started from calculating the total load estimation, calculating battery capacity, determining the peak wattage value of the PV module, determining the inverter, determining the SCC, to designing the physical power of the Solar Power Tree. The result was a design of Solar Power Tree having capacity of 2 kWh with a total estimated load of 1896 Wh.